Perform the indicated operation. (2u^2 - 7) ÷ (u + 3)
(2u^2 - 7) ÷ (u + 3) = (2u^2/u+3) - (7/u+3) = 2u - 6 R. 11
Question
Updated 4/20/2016 6:44:37 PM
Edited by Andrew. [4/20/2016 6:44:37 PM]
f
Rating
8
(2u^2 - 7) ÷ (u + 3)
= (2u^2/u+3) - (7/u+3)
= 2u - 6 R. 11

Questions asked by the same visitor
Perform the long division (y^3 - 125) ÷ (y - 5) User: Multiply (6z^2 - 4z + 1)(8 - 3z)
Weegy: (6z^2 - 4z + 1)(8 - 3z) = -18z^3 + 60z^2 - 35z + 8 User: Simplify b(a + b) - a(a - b). Weegy: b(a + b) - a(a - b) = ab + b^2 - (a^2 - ab) = ab + b^2 - a^2 + ab = 2ab + b^2 - a^2 (More)
Question
Updated 3/9/2016 11:05:33 PM
(y^3 - 125)/(y - 5)
= (y - 5)(y^2 + 5y + 25)/(y - 5)
= y^2 + 5y + 25
Confirmed by Andrew. [3/9/2016 11:05:57 PM]
Simplify 5 + 2{x - 4[3x + 7(2 - x)]}.
Weegy: 5 + 2{x - 4[3x + 7(2 - x)]} = (2x + 32x) + (5 - 112) = 34x - 107 User: Find the product. (7q - 5)(7q + 5) Weegy: (7q - 5)(7q + 5) = 49q^2 + 35q - 35q - 25 = 49q^2 - 25 User: Find the quotient. (35n^3 - 30n^2 + 25n) ÷ (-5n) Weegy: (35n^3 - 30n^2 + 25n) ÷ (-5n) = -7n^2 + 6n - 5 User: Find the product. -2x(x^2 - 3) User: Find the product. -mnp(3m - 5n + 7p) (More)
Question
Updated 3/9/2016 11:02:21 PM
-2x(x^2 - 3)
= -2x*x^2 + (-2x)*(-3)
= -2x^3 + 6x
Confirmed by Andrew. [3/9/2016 11:02:45 PM]
-mnp(3m - 5n + 7p)
= -mnp*3m + mnp*5n - mnp*7p
= -3m^2np + 5mn^2p - 7mnp^2
Confirmed by Andrew. [3/9/2016 11:03:23 PM]
Factor 9y2 - 12y + 4
Weegy: The factored form of 9y^2 - 12y + 4 is (3y-2)^2 User: The area of a square is found by squaring one of its sides, (A = s2). A certain square has an area of z2 + 18z + 81. Factor the trinomial to find a side of the square Weegy: z^2+18z+81 = (z + 9)^2 User: Factor 64 - x2. Weegy: 64 - x^2 = (8 + x)(8 - x) User: Factor x10 - y2. Weegy: x^10 - y^2 = (x^5 + y)(x^5 - y) User: Factor 0.04m 2 - n 2 Weegy: 0.04m^2 - n^2 = (0.2m - n)(0.2m + n) User: Factor 1 - 2.25x8. User: Factor 4a2 - 25. Weegy: 4a^2 - 25 = (2a + 5)(2a - 5) User: x^2 - 9 (More)
Question
Updated 3/10/2016 3:52:11 AM
1 - 2.25x^8
= 1 - (1.5x^4)^2
= (1 - 1.5x^4)(1 + 1.5x^4)
Confirmed by jeifunk [3/10/2016 3:51:58 AM]
x^2 - 9
= x^2 - 3^2
= (x - 3)(x + 3)
Confirmed by jeifunk [3/10/2016 3:52:11 AM]
39,168,116
*
Get answers from Weegy and a team of really smart live experts.
Popular Conversations
*
Get answers from Weegy and a team of really smart live experts.
S
L
Points 1635 [Total 1635] Ratings 0 Comments 1635 Invitations 0 Offline
S
L
Points 1210 [Total 1609] Ratings 3 Comments 1180 Invitations 0 Offline
S
L
Points 706 [Total 706] Ratings 0 Comments 706 Invitations 0 Offline
S
L
Points 394 [Total 394] Ratings 0 Comments 394 Invitations 0 Offline
S
L
Points 209 [Total 3651] Ratings 0 Comments 209 Invitations 0 Offline
S
L
Points 153 [Total 258] Ratings 0 Comments 153 Invitations 0 Offline
S
L
Points 32 [Total 437] Ratings 0 Comments 32 Invitations 0 Offline
S
L
1
1
1
1
Points 20 [Total 2346] Ratings 2 Comments 0 Invitations 0 Online
S
L
1
Points 19 [Total 641] Ratings 0 Comments 19 Invitations 0 Offline
S
L
P
Points 14 [Total 1112] Ratings 0 Comments 14 Invitations 0 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.